Moving from the brown economy to the green economy: the battle over international intellectual property - Ma, J (Brill, 2022)
The article analyses potential intellectual-property-related disputes amid transfer of technology in the green economy within the international investment legal regime. Intellectual property rights (IPRs) protect human innovation and intellectual efforts. Tech transfer, IPRs in particular, has an important role to play in the move towards the green economy. In reality, it is the ‘private-sector-driven’ approach – foreign investment, licensing, and export – that plays the dominant role in tech transfer. Previously, private investors had brought disputes over intellectual property (IP) in the international investment legal regime. Towards the green economy, this article argues that tech transfer in the green economy can still meet more complicated challenges in the international investment legal regime due to the nature of IPRs, the sources of green tech, and the characteristics of the climate crisis.